Gujarat Harappan Connection with West Asia: A Reconsideration of the Evidence - Chakrabarti, Dilip K.
Comments on Romila Thapar, A Possible Identification of Meluḫḫa, Dilmun and Makan, JESHO, 18, 1975, pp. 1-42.